2016
DOI: 10.3389/fpls.2016.01784
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Virulence Factors in Leptosphaeria maculans during Compatible and Incompatible Interactions with Canola

Abstract: Leptosphaeria maculans is a hemibiotrophic fungus that causes blackleg of canola (Brassica napus), one of the most devastating diseases of this crop. In the present study, transcriptome profiling of L. maculans was performed in an effort to understand and define the pathogenicity genes that govern both the biotrophic and the necrotrophic phase of the fungus, as well as those that separate a compatible from an incompatible interaction. For this purpose, comparative RNA-seq analyses were performed on L. maculans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 69 publications
3
58
0
1
Order By: Relevance
“…triticale genome shows a hybrid architecture with segments originating from the wheat mildew donor and others from the rye mildew donor, with a very variable origin of the different segments in different isolates (Menardo et al, 2016 ). Many published RNAseq studies compared gene expression levels of the same fungal genotype under different conditions, at different times after infection, or between compatible and incompatible interactions (Cantu et al, 2013 ; Hacquard et al, 2013 ; Kellner et al, 2014 ; Palma-Guerrero et al, 2016 ; Sonah et al, 2016 ). In our work, we used a reference genome-based approach allowing both intra- and inter- forma specialis comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…triticale genome shows a hybrid architecture with segments originating from the wheat mildew donor and others from the rye mildew donor, with a very variable origin of the different segments in different isolates (Menardo et al, 2016 ). Many published RNAseq studies compared gene expression levels of the same fungal genotype under different conditions, at different times after infection, or between compatible and incompatible interactions (Cantu et al, 2013 ; Hacquard et al, 2013 ; Kellner et al, 2014 ; Palma-Guerrero et al, 2016 ; Sonah et al, 2016 ). In our work, we used a reference genome-based approach allowing both intra- and inter- forma specialis comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcriptomic studies in biotrophic fungal pathogens such as Puccinia striiformis , as well as hemibiotrophs such as Magnaporthe grisea, Zymoseptoria tritici , and Leptosphaeria maculans all found strong upregulation of putative effector genes during host infection, thus substantiating their role in host-pathogen interactions (Kawahara et al, 2012 ; Garnica et al, 2013 ; Hacquard et al, 2013 ; Sonah et al, 2016 ). It was also shown that effector gene expression in plant pathogenic fungi occurs in different waves during host invasion, suggesting stage-specific regulation of different subsets of the effector repertoire (Cantu et al, 2013 ; Hacquard et al, 2013 ; Rudd et al, 2015 ; Palma-Guerrero et al, 2016 ; Sonah et al, 2016 ). In Leptosphaeria maculans , stage-specific expression of different effector waves was identified in transcriptomic studies comparing cotyledon and stem colonization of oilseed rape by the pathogen (Sonah et al, 2016 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A heat map for expression of AQPs was constructed using TIGR Multi Experiment Viewer (MeV 4 ). Hierarchical clustering with average linkage method was performed to cluster the genes ( Sonah et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…QTL regions are quite large, and harboring too many genes makes it difficult to identify the candidate gene, but the combination of QTL and GWAS approaches has been successfully used to identify candidate genes in soybean [107]. Furthermore, the integration of RNA sequencing profiles with gene expression profiles can provide vital clues for the identification of functions of unknown genes [108,109]. Therefore, combining QTL and GWAS with transcriptome profiling will be helpful to identify differentially expressed candidate genes [110,111].…”
Section: Integration Of Omics Technologiesmentioning
confidence: 99%